Penerapan Student Facilitator And Explaining pada Peningkatan Keaktifan, Motivasi, dan Hasil Belajar IPS - Wahyu Setyawati; Esti Setiawati (Proceedings Series on Social Sciences & Humanities, 2022)
This research aimed to increase activeness, motivation, and social studies learning outcomes through the application of the Student Facilitator and Explaining model to fifth-grade students at SD Negeri Tunggorono Purworejo for the 2021/2022 academic year. This type of research is classroom action research. The research subjects were students of class V SD Negeri Tunggorono, totaling 12 students. The research stages include 4 stages, namely planning, implementation, observation, and reflection. Data collection techniques using documentation, questionnaires, observations, and tests. The data analysis technique used was descriptive quantitative with percentages. The results showed that 1) the use of the Student Facilitator and Explaining learning model could increase the activeness of students in the high category, from 33.33% in the pre-cycle, to 66.67% in the first cycle and 91.67% in the second cycle; 2) the use of the Student Facilitator and Explaining learning model can increase the motivation of students in the high category from 41.67% in the pre-cycle, to 75% in the first cycle and 91.67% in the second cycle; 3) the use of the Student Facilitator and Explaining learning model can improve the social studies learning outcomes of students who complete the pre-cycle by 33.33%, increase to 75% in the first cycle, and become 100% in the second cycle.